2020
DOI: 10.1111/aeq.12360
|View full text |Cite
|
Sign up to set email alerts
|

Transfronterizo Children’s Literacies of Surveillance and the Cultural Production of Border Crossing Identities on the U.S.–Mexico Border

Abstract: This article examines the cultural production of three transfronterizo children who daily, physically cross a U.S.–Mexico international bridge. Drawing on theories of identity, border inspections, literacy, and language, the findings reveal that transfronterizo children developed literacies of surveillance, or the acquired and produced language and literacy practices to move across the surveillance, inspectors, and border. Transfronterizo children strategically used their full linguistic repertories to legitim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Las escuelitas did not serve as out-of-school practices but were the participants’ first school, sanctioned by the parents to teach Spanish literacy. As discussed in more recent work by Nuñez and Urrieta (2021) and de la Piedra and Guerra (2012), las escuelitas depict a shift in ways of knowing and being in the borderlands that counter macro discourses and practices of English hegemony. Border people blur national boundaries and languages, drawing from complex and dynamic “unofficial” literacy practices and subaltern knowledge—such as border-crossing, religious, and musical literacies—in tandem with schooling literacy experiences, to assume and enact bilingual and biliterate subjectivities (de los Ríos, 2017; Harvey-Torres & Degollado, 2021).…”
Section: Descents and Emergences: Toward Border Thinking Epistemologiesmentioning
confidence: 99%
“…Las escuelitas did not serve as out-of-school practices but were the participants’ first school, sanctioned by the parents to teach Spanish literacy. As discussed in more recent work by Nuñez and Urrieta (2021) and de la Piedra and Guerra (2012), las escuelitas depict a shift in ways of knowing and being in the borderlands that counter macro discourses and practices of English hegemony. Border people blur national boundaries and languages, drawing from complex and dynamic “unofficial” literacy practices and subaltern knowledge—such as border-crossing, religious, and musical literacies—in tandem with schooling literacy experiences, to assume and enact bilingual and biliterate subjectivities (de los Ríos, 2017; Harvey-Torres & Degollado, 2021).…”
Section: Descents and Emergences: Toward Border Thinking Epistemologiesmentioning
confidence: 99%
“…Scholars have demonstrated how birth certificates, passports, and other identification cards are the texts—papeles—that facilitate (or inhibit) movement across nations and institutions (Mangual Figueroa, 2012; Nuñez & Urrieta, 2021; Vieira, 2016). Papeles are written texts requiring a specific set of literacy skills to access tangible rights.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A rich body of scholarship in anthropology and education exploring the language and literacy practices of transnational youths has shown that multilingual Latinx adolescents are often engaged in such practices outside of school spaces; these practices are not often recognized by or built upon in the classroom despite the potential they have for supporting students in bridging knowledge and experience. For example, examining the literacy and languaging practices of transfronterizo children—children who cross the U.S.–Mexico border and experience daily life on both sides of the border (Martínez, 1994)—Nuñez and Urrieta (2020) described how, as border crossers, these young children developed literacies of surveillance, or literacy knowledges needed for navigating surveillance and inspectors as they moved across borders. Nuñez and Urrieta noted that children relied on and utilized knowledge from across their linguistic repertoires in these encounters and experiences.…”
Section: Contextual Informationmentioning
confidence: 99%